Inadequate Hand Washing, Lack of Clean Drinking Water and Latrines as Major Determinants of Cholera Outbreak in Somali Region, Ethiopia in 2019 - Challa, Jemal Mussa; Getachew, Tamirat; Debella, Adera; Merid, Melkamu; Atnafe, Genanaw; Eyeberu, Addis; Birhanu, Abdi; Regassa, Lemma Demissie (Frontiers in Public Health, 2022)
Introduction: Cholera remains a serious public health problem characterized by a large disease burden, frequent outbreaks, persistent endemicity, and high mortality, particularly in low-income countries including Ethiopia. The recent cholera outbreak in the Somali region started on 4 September to 1 November 2019. Because cholera can spread rapidly through a population, early detection of cases is mandatory. Thus, the study aimed to identify determinants of cholera outbreak among >5 years of age population in Somali region, Ethiopia. Methods: A community-based unmatched case-control study was used among 228 (76 cases and 152 controls, 1:2 ratio) systematically selected population. Data were collected using a structured questionnaire administered by an interviewer and a record review. Multivariate logistic regression analysis was used to identify the determinants of the cholera outbreak with a 95% confidence interval and statistical significance was declared at a p-value <0.05. Results: A total of 228 participants (33.3% cases and 66.7% controls) were included in the analysis. The cholera outbreak was significantly associated with low monthly income, drinking unsafe water, knowledge of cholera, open defecation, hand washing before cooking and after the toilet, and using water purification methods. Conclusion: A total of 110 (AR=0.16%) cholera cases and 1 death were reported. Improvement in awareness creation about cholera prevention and control methods, including water treatment, hygiene, and sanitation, was crucial to combating the cholera outbreak. Overall, the strategic role of a multi-sectoral approach in the design and implementation of public health interventions aimed at preventing and controlling cholera is essential to avert the outbreak